2016
DOI: 10.1186/s40101-016-0097-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the kindergarten barefoot policy on preschool children’s toes

Abstract: BackgroundThis study compared the effects of barefoot policy, a policy instructing preschool children to go without shoes, on untouched-toes, which do not touch the ground while standing normally, of preschool children attending kindergartens that follow this rule, to preschooler in kindergartens where they must wear shoes, i.e., no-barefoot policy.MethodsThe study used longitudinal data from measurements taken 2 years apart of the amount of times. The subjects were 59 children (34 boys and 25 girls) who went … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…On the other hand, girls' foot angle showed no significant difference. The barefoot policy's effects were found in non-touching toes and anterior−posterior foot pressure ratio only for boys Matsuda, Kasuga, Hanai, Demura, & Futabayashi, 2016;Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). In other words, gender differences may exist in effects of barefoot pol-icy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, girls' foot angle showed no significant difference. The barefoot policy's effects were found in non-touching toes and anterior−posterior foot pressure ratio only for boys Matsuda, Kasuga, Hanai, Demura, & Futabayashi, 2016;Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). In other words, gender differences may exist in effects of barefoot pol-icy.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported effects of barefoot policy on "non-touching" toes, those that do not touch the ground during standing, and the anterior-posterior foot pressure ratio Matsuda, Kasuga, Hanai, Demura, & Futabayashi, 2016;Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). Research revealed that boys who attended kindergartens following barefoot policy had fewer non-touching toes and lower posterior foot pressure ratio than those who attended kindergartens not following the policy Matsuda, Kasuga, Hanai, Demura, & Futabayashi, 2016;Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). Although some effects of barefoot policy have been previously examined, its effects require multilateral examination in order to judge pros and cons comprehensively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some kindergartens in Japan follow a policy according to which children play barefoot when playing indoors after arriving at their kindergartens. This barefoot policy has been adopted because of the belief that it positively affects children's health and growth by influencing the foot shape (medial longitudinal arch and foot width) and the contact between their toes and the ground (Asami, Ishijima, & Shibukawa, 1990;Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). However, the actual effects of kindergartens' barefoot policies, beyond their influence on the shape of children's feet and toes, have seldom been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Children who attend kindergartens following a barefoot policy have fewer untouched toes because they have greater opportunities to move their toes Matsuda, Kasuga, Hanai, Demura, & Komura, 2016). As the anterior foot pressure ratio increases as more toes touch the ground, it is hypothesized that children who attend kindergartens following a barefoot policy have a higher anterior foot pressure ratio and do not tend to have heel load.…”
Section: Introductionmentioning
confidence: 99%